Застосування тривимірної графіки в медицині - Лисиченко, В. О. (My University, 2021)
3D modeling is the process of creating a detailed, three-dimensional model of any object, including the organs of any living being. The task of 3D modeling is to develop a visual three-dimensional image, the desired object. In fact, three-dimensional objects can be human organs, both men and women.
Keywords: 3D моделювання; медицина